On the Quantum Spin Hall Gap of Monolayer 1T′‐WTe2. Issue 24 (26th April 2016) - Zheng, Feipeng; Cai, Chaoyi; Ge, Shaofeng; Zhang, Xuefeng; Liu, Xin; Lu, Hong; Zhang, Yudao; Qiu, Jun; Taniguchi, Takashi; Watanabe, Kenji; Jia, Shuang; Qi, Jingshan; et al.
Abstract : Positive quantum spin Hall gap in monolayer 1T ′‐WTe2 is consistently supported by density‐functional theory calculations, ultrafast pump–probe, and electrical transport measurements. It is argued that monolayer 1T′‐WTe2, which was predicted to be a semimetallic quantum spin Hall material, is likely a truly 2D quantum spin Hall insulator with a positive quantum spin Hall gap.